274 Improved beef quality and yield in Wagyu compared to Angus sired cattle unaffected by protein supplementation during the late gestation. (5th December 2019) - Liu, Xiangdong; Moffitt-Hemmer, Natasha; Deavilla, Jeanene; Neibergs, Shannon; Busboom, Jan; Nelson, Mark; Du, Min
Abstract: Maternal nutrition during the late gestation affects marbling fat in offspring. Wagyu cattle are well known for their very high marbling with more unsaturated fatty acid contents, but they grow slower than Angus cattle. The interaction between maternal diet and breed on marbling fat development is unclear. To examine, Angus cows (621 ± 73kg) were selected and separated into two groups, bred with either Angus or Wagyu semen. During the last 90 d of gestation, cows in each group were further separated and received either a low protein diet (85% of the NRC metabolizable protein requirement), which mimics the protein intake common in Northwestern region when fed a wheat straw based diet, or a high protein diet (108% NRC requirement). All progeny were managed together and harvested at a final body weight of 576.5± 16.6 kg. For Wagyu sired offspring, marbling score and quality grade was higher than Angus (P < 0.01), and also had higher Ribeye area (P = 0.07). The marbling scores were higher for the low protein diet for all except Wagyu steers. No difference was detected in KPH fat and the yield grade was higher for Wagyu sired cattle than Angus (P < 0.01). In both diets, Angus offspring showed higher shear force (P < 0.05). When grouped according to sex, higher marbling was observed in heifers (P < 0.01). No difference was found in cooking yield, drip loss, but Wagyu sired offspring had thicker back fat than Angus (P < 0.01). Within the high protein diet, Wagyu beef had higher linoleic acid content compared to Angus (P < 0.05). In conclusion, Wagyu sired cattle had better quality and yield compared to Angus sired, and protein supplementation during the late gestation had no major effect on beef quality. (Supported by the USDA-NIFA grants 2015-67015-23219/2016-68006-24634 to MD)